2009
DOI: 10.1063/1.3089425
|View full text |Cite
|
Sign up to set email alerts
|

The static-exchange electron-water pseudopotential, in conjunction with a polarizable water model: A new Hamiltonian for hydrated-electron simulations

Abstract: Previously, Turi and Borgis [J. Chem. Phys. 117, 6186 (2002)] parametrized an electron-water interaction potential, intended for use in simulations of hydrated electrons, by considering H(2)O(-) in the "static exchange" (essentially, frozen-core Hartree-Fock) approximation, then applying an approximate Phillips-Kleinman procedure to construct a one-electron pseudopotential representing the electron-water interaction. To date, this pseudopotential has been used exclusively in conjunction with a simple point cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(91 citation statements)
references
References 83 publications
3
87
0
1
Order By: Relevance
“…This is called the cavity model of the hydrated electron. Theoretically, this cavity can be described by pseudopotentials [21,19,22]. Corresponding simulations agree reasonably well with experiments.…”
Section: Discovery and Importance Of Solvated Electronssupporting
confidence: 64%
“…This is called the cavity model of the hydrated electron. Theoretically, this cavity can be described by pseudopotentials [21,19,22]. Corresponding simulations agree reasonably well with experiments.…”
Section: Discovery and Importance Of Solvated Electronssupporting
confidence: 64%
“…65,66 Another recent study pointed out the role of polarizable water models, which may also be potentially important for all cluster sizes. 67 The electron-water molecule model has nonetheless become successful. Ab initio test calculations indicated that the small cluster behavior is still reasonable, showing a reasonably linear correlation between the ab initio stabilization energies and those calculated with the pseudopotential.…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of the latter two features has been noted in work examining water-cluster anions (3,19), these features have not been incorporated into the pseudopotentials in previous bulk e − aq simulations (1, 2), so their importance to the behavior of the bulk hydrated electron has not been explored. Thus, to account for the presence of these features, we have fitted our potential to a sum of hydrogen-and oxygencentered terms, plus a sum of terms centered midway between the two hydrogen atoms; the fit is shown in the right panels of Fig.…”
Section: Downloaded Frommentioning
confidence: 99%
“…The effect that the hydrated electron has on the structure of the nearby water molecules is summarized in Fig. 2D, which shows water-water RDFs for water molecules inside the electron (within 3.25 Å of the electron's COM, middle curves) and those in pure water at both normal (1.00 g/cm 3 , lower curves) and higher (1.23 g/cm 3 , upper curves) densities. Clearly, the water molecules inside the electron are packed together more like water at high density than like water at normal density.…”
Section: Downloaded Frommentioning
confidence: 99%